Business models for strategic innovation : cross-functional perspectives - Shams, S. M. Riad, 1979- editor; Weber, Yaakov; Vrontis, Demetris editor; Tsoukatos, Evangelos editor (Abingdon, Oxon ; New York, NY : Routledge, 2018)
Includes bibliographical and references